Learning of similar complex movement sequences: proactive and retroactive effects on learning - Panzer, S.; Wilde, H.; Shea, C. H. (Journal of Motor Behavior, 2006)
The authors used an interference paradigm to determine the extent to which the learning of 2 similar movement sequences influences the learning of each other. Participants (N=30) produced the sequences by moving a lever with their right arm and hand to sequentially presented target locations. They practiced 2 similar 16-element movement sequences (S1 and S2), 1 sequence on each of 2 consecutive days of practice. Control groups received only 1 day of practice on 1 of the sequences. Early in S2 practice, the experimental group demonstrated a relatively strong level of proactive facilitation arising from previous practice with S1. The advantage was not evident at the end of S2 practice or on the S2 retention test. No advantage of practicing the 1st sequence on the learning of the 2nd sequence (proactive effect) was found in the analysis of element duration in the retention and transfer tests, even though 14 of the 16 elements were common to both sequences. A strong retroactive interference on the switched elements was detected, however. Thus, the memories underpinning S1 seemed to be "overwritten" or adapted in response to the learning of S2.